The Mission : inside the Church of Jesus Christ of Latter-day Saints - Naythons, Matthew; Harper, Acey.; Hinckley, Gordon Bitner, 1910-2008.; Rosenblatt, Roger; Epicenter Communications (Firm) (New York : Warner Books, 1995)
Photographs of Mormons taken by 50 of the world's most talented photographers during the course of one year, on six continents, recording missions, weddings, funerals, family home evenings, home and community life.
Introduction: Why am I a member of the Church of Jesus Christ of Latter-day Saints? / Gordon B. Hinckley -- Major events in the history of the Church of Jesus Christ of Latter-day Saints -- Families are forever: Faith begins at home: Photo essay, Baptism in Alaska / Rich Frishman -- A new generation: Photo essay, Following the pioneers / Paul Chesley -- An eternal chain: Photo essay, A young father's funeral / Joel Sartore -- A new church for a new land: Following the prophets: Photo essay, When the Saints meet... / Acey Harper, Joel Sartore, Ed Kashi -- A good way of life: Photo essay, Pilgrimage down the Amazon / Claus Meyer -- Spreading the word: A ministry of love and faith: Photo essay, Prison ministry / Joel Sartore -- Photo essay, Convoy to Croatia / Barry Lewis -- The mission: Photo essay, Emissaries to Moscow / Nikolai Ignatiev -- Photo essay, The making of a missionary / Acey Harper -- Epilogue: Images of faith / Roger Rosenblatt.
"An Epicenter Communications book"
Keywords: Church of Jesus Christ of Latter-day Saints -- Pictorial works; Latter Day Saint churches -- Pictorial works